The in vitro activity of delafloxacin and comparator agents against bacterial pathogens isolated from patients with cancer. Issue 2 (27th March 2023) - Gerges, Bahgat; Rolston, Kenneth; Shelburne, Samuel A; Rosenblatt, Joel; Prince, Randall; Raad, Issam
Abstract: Background: Fluoroquinolones are used for infection prevention in high-risk patients with haematological malignancies. Fluoroquinolones are active against many Gram-negative bacilli (GNB) but are less active against Gram-positive organisms. We evaluated the in vitro activity of delafloxacin and selected comparators against 560 bacterial pathogens isolated exclusively from patients with cancer. Methods: Antimicrobial susceptibility testing and time-kill studies were performed using CLSI-approved methodology and interpretive criteria for 350 Gram-positive organisms and 210 GNB that had been recently isolated from patients with cancer. Results: Delafloxacin was more active than ciprofloxacin and levofloxacin against Staphylococcus aureus and CoNS. Overall, 63% of staphylococcal isolates were susceptible to delafloxacin, 37% to ciprofloxacin and 39% to levofloxacin. Activity of delafloxacin against most Enterobacterales was similar to that of ciprofloxacin and levofloxacin. Escherichia coli and MDR Pseudomonas aeruginosa isolates had low susceptibility rates to the three tested fluoroquinolones. In time-kill studies delafloxacin and levofloxacin decreased the bacterial load to 3.0 log10 in 8 and 13 h, respectively, using 8 × MIC. Conclusions: Delafloxacin is more active than ciprofloxacin and levofloxacin against S. aureus but has substantial gaps in coverage against GNB. Resistance to all three fluoroquinolones could be high among leading GNB such as E. coli and P. aeruginosa, particularly in cancer centres where these agents are widely used as prophylactic agents.